Should Islamic finance be different from conventional finance both in form an substance ?Viewpoints / Badlisyah Abdul Ghani - Abdul Ghani, Badlisyah (Universiti Teknologi Mara Selangor, 2013)
viewpoints should Islamic finance be different from conventional finance both in form and substance? and is there such a thing as Islamic accounting in Islamic banking and finance industry.